Addition of L-Tryptophan in Feed to Reduce the Cannibalism of Asian Redtail Catfish (Hemibagrus nemurus) Seeds - Rafi Maulana Rasyad; Lukman Anugrah Agung; Mas Bayu Syamsunarno; Mustahal Mustahal; Saifullah Saifullah (JURNAL PERIKANAN DAN KELAUTAN, 2025)
Fullfillment of asian redtail catfish needs in the market can be done by cultivation. The limited availability of Asian redtail catfish seeds has always been an obstacle for cultivators due to cannibalism in the larval to seed stages. One effort to reduce cannibalism in asian redtail catfish seeds is the addition of L-tryptophan which functions as a serotonin hormone synthesis so that it can reduce aggresiveness. However, giving L-Tryptophan in excessive doses can inhibit the growth rate of fish. Therefore this research aims to determine the best dose in reduce cannibalism without inhibiting the growth rate. The research was conducted in July-November 2023, located at the BRIN mini hatchery, Tajurhalang, Bogor. This research used a completely randomized design (RCD) consisting of five different L-Tryptophan dose treatments and was repeated three times. The doses used were 0%, 0,5%, 0,6%, 0,7%, 0,8% (% /kg of feed). This research consisted of four stages, namely preparation of containers, distribution of experimental fish, preparation of treatment feed and maintenance of experimental fish. The results of this research indicated the addition of L-Tryptophan at highest doses (0,8% /kg of feed) is the best treatment to reduce the cannibalism of asian redtail catfish seeds without inhibiting growth. It has the best survival rate value 94,07%, normal death 2,22%, the lowest cannibalism index of 3,70%, the lowest type 1 cannibalism of 3,70%, and no type 2 cannibalism incidents. Water quality during the research was still on the threshold of the optimum maintenance of asian redtail catfish seeds.